Taxation of Permanent Establishments in Ukraine: Unresolved Issues - Trachuk, Vitalii; Franchuk, Khrystyna (Kyiv-Mohyla Law and Politics Journal, 2018)
This article deals with selected issues of taxation of permanent establishments in Ukraine that lack appropriate judicial and scholarly attention. It particularly focuses on the attribution of profits to permanent establishments according to OECD standards and Ukrainian law, taxation of dependent agent permanent establishments, and the State’s taxing rights with respect to the permanent establishment’s financing by its head office. The authors conclude that to improve the quality of permanent establishments’ taxation in Ukraine, appropriate procedures should be clearly prescribed in the law and due regard be given to the already developed international standards that might be, in fact, directly applicable.